PRMT5-mediated regulation of developmental myelination - Antonella Scaglione (Nature Portfolio, 2018)
Myelin-forming cells derive from oligodendrocyte progenitors. Here the authors identify histone arginine methyl-transferase PRMT5 as critical for developmental myelination by modulating the cross-talk between histone arginine methylation and lysine acetylation, to favor differentiation.